ANALYSIS OF PROSPECTS OF APPLICATION OF POLYMERIC MATERIALSFOR THE MANUFACTURE OF NUCLEAR PROTECTIVE CLOTHING - ZAKHARKEVICH, Oksana; KULESHOVA, Svitlana; TKACHUK, Serhii; LUKYANCHUK, Svitlata (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article is devoted to identifying the main ways to improve the design and manufacture of clothing for nuclear power plant workers to ensure the competitiveness of domestic products. The scientific novelty of the work is that it further developed the issue of systematization of the range of nuclear protective clothing, which identified ways to improve its design processes in the domestic garment industry. The practical significance of the work lies in the use of polymeric materials in the designed methods of processing the components of the developed suit of nuclear protective clothing. The authors analyze the current state of research in the design and manufacture of nuclear protective clothing. Depending on the work performed, the range of nuclear protective clothing is considered from the standpoint of the materials used. The world leaders producing nuclear protective clothing are 3M; Lakeland; DuPont; Honeywell; Microgard; Delta Plus; Kappler; Casco; MATISEC; VersarPPS. According to the results of the analysis of the range of nuclear protective clothing, it is determined that the vast majority of manufacturers focus on the materials from which nuclear protective clothing is made to protect against radiation pollution and other harmful factors. As a result of scientific research, the basic approaches of the world leaders-manufacturers of nuclear protective clothing concerning the connection of details of products are defined. A database of seams used to make nuclear protective clothing has been formed. Among the variety of protective clothing, the basic design and technological solutions of protective clothing are identified as those that most fully protect against certain types of hazards for various industries in terms of passive methods of employee protection. The selected range of basic protective clothing includes suits and varieties of pants and jackets. A men's jacket as a part of nuclear protective clothing is proposed, and methods of processing the product's main components based on the use of polymeric materials are improved. Sealing the joints of the product parts using a film with a polymer coating is suggested. The authors have formulated requirements for materials used for the manufacture of suits for nuclear power plant workers: indicators of physical and mechanical, and physicochemical properties of materials for manufacturing white suits.
Keywords: nuclear protective clothing; sealing the seams; polymeric materials